Effect of Calcium Hydroxide and Nano Calcium Hydroxide on Push-out Bond Strength of Epoxy Resin Sealer to Root Canal Dentin - Sahebi, Safoora; Asheghi, Bahar; Samadi, Yasser; Eskandari, Fateme (Iranian Endodontic Journal, 2022)
Introduction: The goal of this paper was to determine the impact of calcium hydroxide (CH) and nano-calcium hydroxide (NCH) on the push-out bond strength of an epoxy resin-based sealer. Materials and Methods: A total of 48 mandibular premolars were decoronated in vitro and instrumented by a ProTaper rotary system up to F4. The specimens then were randomly allocated into 3 groups (n=16). The two intervention groups were treated with either CH or NCH and one control group which did not receive any intracanal medicament. After one week of medicament placement, the specimens were irrigated by 10 mL 17% EDTA, followed by 10 mL 2.5% NaOCl and an ultimate flushing by 5 mL sterile saline. The samples were obturated using AH-Plus Jet sealer and gutta-percha by lateral condensation technique. Push-out test was done by a universal test machine to evaluate the bond strength among the sealer and the root canal dentin. Repeated measurement analysis followed by Tukey’s HSD and Bonferroni post-hoc tests were used for data analysis. Results: The control group showed a higher push-out bond strength in comparison to the specimens in the CH and NCH groups (P<0.05). In spite of the greater push-out bond strength of the samples treated with NCH in comparison to those in CH group, no statistically notable difference was found among them (P>0.05). Additionally, irrespective of the kind of medicament, the bonding at the apical level of the root canal was stronger compared to the coronal third (P<0.001). Conclusion: According to the present in vitro study, application of CH and NCH resulted in a significant reduction of the bond strength between the epoxy resin-based sealer and dentinal walls. Although, application of these medicaments resulted in reduction of bonding of epoxy resin-based sealers root canal dentin significantly.